Faktor-Faktor Yang Memperngaruhi Etika Pada Mahasiswa Akuntansi Syariah - Wahid Wachyu Adi Winarto; Ina Mutmainah (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
ABSTRACT This research is a study that discusses the intelligence of Islamic accounting students who will later be able to cultivate the accounting profession which is closely related to professional ethics. This study aims to analyze intellectual intelligence, emotional intelligence, spiritual intelligence and social intelligence in Islamic accounting students on professional ethics if they become an accountant. The data obtained in the study using a questionnaire distributed to respondents. The sample in this study were 98 students of Islamic accounting at FEBI IAIN Pekalongan. The sampling method used was purposive sampling and the data were analyzed using SPSS 20. The results of the analysis show that the factors that influence ethics in Islamic accounting students are intellectual intelligence, emotional intelligence, spiritual intelligence and social intelligence. Partially only emotional intelligence has a positive and significant effect on ethics in sharia accounting students. This study provides input that improving the quality of students with improved emotional intelligence can provide good professional ethical quality.